2021
DOI: 10.3390/pediatric13040074
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine–Flecainide as Breakthrough Drug Combination for Congenital Junctional Ectopic Tachycardia: A Case Report and Literature Review

Abstract: Congenital junctional ectopic tachycardia (CJET) is a rare tachyarrhythmia that remains difficult to manage, with suboptimal control in most cases. Here, we report literature research on the use of ivabradine in the treatment of pediatric junctional ectopic tachycardia (JET), both congenital and postoperative, and describe the successful use of ivabradine–flecainide association for CJET therapy resistant to other antiarrhythmic agents. This new drug combination was effective in completely suppressing JET. Ivab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“… 22 Recently, enteral ivabradine administered alone or in combination with other medications (amiodarone, flecainide) has been shown to be effective. 13 , 16 , 23 To date, there have been no reports using ivabradine in combination with procainamide for the management of postoperative JET. We describe a patient with JET refractory to initial measures with a progressively worsening postoperative status, in whom the addition of ivabradine to procainamide proved effective and safe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 Recently, enteral ivabradine administered alone or in combination with other medications (amiodarone, flecainide) has been shown to be effective. 13 , 16 , 23 To date, there have been no reports using ivabradine in combination with procainamide for the management of postoperative JET. We describe a patient with JET refractory to initial measures with a progressively worsening postoperative status, in whom the addition of ivabradine to procainamide proved effective and safe.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Additionally, prior case studies have described the benefits of amiodarone or flecainide in conjunction with ivabradine for the treatment of postoperative and congenital JET. 16 , 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ivabradine may cause negative inotropic and vasoconstrictive effects, arrhythmias, impaired intracardiac impulse propagation, or arterial hypotension. Rarely, dysphagia has been reported [5][6][7][8][9]. Case reports show beneficial effects in tachyarrhythmias, showing no increase in adverse events compared to use in adults.…”
Section: Review On Antiarrhythmic Drug Dosing In Childrenmentioning
confidence: 99%
“…The overall incidence of dysrhythmias is 55.1 per 100,000 pediatric ED visits [ 1 ]. Nevertheless, the pediatric ED physician should be able to determine whether child requires immediate examination and referral to a cardiologist [ 2 , 3 ]. Sacchetti et al [ 4 ] conducted a retrospective review of cardiac dysrhythmias in children presenting to the ED, and revealed that sinus tachycardia was the most commonly reported dysrhythmia (50%), followed by supraventricular tachycardia (13%), nonspecific dysrhythmias (10.6%), bradycardia (6%), and atrial fibrillation (4.6%).…”
Section: Introductionmentioning
confidence: 99%